Predictors of 1-Year Global Outcomes After Traumatic Brain Injury Among Older Adults: A NIDILRR Traumatic Brain Injury Model Systems Study. (December 2019) - Hammond, Flora M.; Baker-Sparr, Christina A.; Dahdah, Marie N.; Dams-O'Connor, Kristen; Dreer, Laura E.; O'Neil-Pirozzi, Therese M.; Novack, Thomas A.
Objective: To assess predictors of global function and driving status among older adults (50 years and older) who survived 1 year following inpatient rehabilitation for moderate-to-severe traumatic brain injury (TBI).Methods: Functional status at 1-year post-TBI was determined for 1, 845 individuals. The relationship age category to function was studied using associations and predictive modeling.Results: The final model accounted for 34% variance in Glasgow Outcome Scale-Extended (GOS-E) among 60- to 69-year-olds and 70- to 79-year-olds, and 25% variance in 50- to 59-year-olds and 80+-year-olds. FIM Motor at rehabilitation discharge made the greatest contribution to GOS-E variance across all age groups. Inpatient rehabilitation discharge to nursing home or adult home and rehospitalization were associated with a one-level decrease in GOS-E. Alcohol use predicted lower GOS-E among the 70- to 79-year-olds. Gender, ethnicity, and rehospitalizations were negatively associated driving.Discussion: Rehabilitation approaches to older adults with TBI may help maximize function and, thereby, improve later outcomes and decrease rehospitlaizations. Such strategies may include longer and more intensive acute rehabilitation with greater patient engagement and enhanced transitions of care.